Inferior Vena Cava Collapsibility Index Can Predict Hypotension and Guide Fluid Management After Spinal Anesthesia - Ni, Ting-ting; Zhou, Zhen-feng; He, Bo; Zhou, Qing-he (Frontiers in Surgery, 2022)
Background: We hypothesized that IVCCI-guided fluid management would reduce the incidence of postspinal anesthesia hypotension in patients undergoing non-cardiovascular, non-obstetric surgery. Methods: A receiver operating characteristic (ROC) curve was used to determine the diagnostic value of IVCCI for predicting hypotension after induction of spinal anesthesia and calculate the cut-off value. Based on the cut-off variation value, the following prospective randomized controlled trial aimed to compare the incidence of postspinal anesthesia hypotension between the IVCCI-guided fluid administration group and the standard fluid administration group. Secondary outcomes included the rate of vasoactive drug administration, the amount of fluid administered, and the incidence of nausea and vomiting. Results: ROC curve analysis revealed that IVCCI had a sensitivity of 83.9%, a specificity of 76.3%, and a positive predictive value of 84% for predicting postspinal anesthesia hypotension at a cut-off point of >42%. The area under the curve (AUC) was 0.834 (95% confidence interval: 0.740–0.904). According to the cut-off variation value of 42%, the IVCCI-guided group exhibited a lower incidence of hypotension than the standard group (9 [15.3%] vs. 20 [31.7%], P=0.032). Total fluid administered was lower in the IVCCI-guided group than in the standard group (330 [0–560] mL vs. 345 [285–670] mL, P=0.030). Conclusions: Prespinal ultrasound scanning of the IVCCI provides a reliable predictor of hypotension following spinal anesthesia at a cut-off point of >42%. IVCCI-guided fluid management before spinal anesthesia can reduce the incidence of hypotension following spinal anesthesia. Clinical Trial Registration: http://www.chictr.org.cn/index.aspx (ChiCTR1900027848).